Governança eclesiástica: um estudo de caso na cúria metropolitana de Fortaleza - Pontes III, Joaquim Fernando (2023)
In Brazil, the Roman Catholic Apostolic Church is classified as the third sector of the national economy, as it deals with private capital, but without a profit motive. Like other contemporary organizations, it is part of an increasingly complex context, in which the professionalization of its activities, through corporate governance practices, applied in the ecclesiastical sphere, is fundamental. The Catholic Church has its own model of corporate governance contained in the Code of Canon Law and in pontifical documents written for this purpose. In line with this context, this research aims to investigate how governance practices occur in a religious institution, in this case in the Metropolitan Curia of Fortaleza. The study has a qualitative and exploratory-descriptive approach, with research subjects being participants linked to the Archdiocese of Fortaleza/CE who occupy leadership roles in the Metropolitan Curia. For data collection, a qualitative adaptation was made, in the form of a semi-structured interview script, of the questionnaire by Nunes and d'Angelo (2020), originally used to measure the Diocese Corporate Governance Index – IDGC, in four dimensions . In analyzing the data, a content analysis was carried out, with support from the Atlas.ti software. The results show that governance practices occur in the Metropolitan Curia of Fortaleza when evaluated in accordance with the dimensions of the Diocese Corporate Governance Index (IGCD) - disclosure, compliance, management mechanisms and performance. This fact demonstrates that the governance profile of the Catholic Church in its district in the capital of Ceará meets the hierarchical instances characteristic of this model of institution, as well as the professionalization of its services demonstrates its growth alongside organizations in the third sector of the national economy. In relation to governance practices in the disclosure dimension, it was found that the institution meets the proposal of disclosing information to interested parties, whether internal or external to the administrative body. Regarding the mechanism dimension, it was found that the Metropolitan Curia meets this criterion to the extent that its services provided are available to the diocesan bishop. Regarding the compliance dimension, it is concluded that the administrative body in question operates in accordance with civil and canonical legislation. And, regarding the performance dimension, it was observed that it meets the specific mission of the Catholic Church in spiritual terms, evident in the evangelizing purpose of its services and the theological foundation of its content. Among the contributions of the study, in theoretical-methodological terms, the fact of adding new data to research on the construction of governance in religious institutions, mainly in terms of Catholic religious confession, stands out, and in the field of management, this research intended to take the framework of the corporate world of companies for the third sector, particularly religious institutions, in this case the Catholic Church.